THE EFFECTIVENESS OF GROUP COUNSELING SERVICES WITH CREATIVE PROBLEM-SOLVING TECHNIQUES TO REDUCE STUDENTS' ACADEMIC STRESS - Siska Astria Br Ginting; Nurussakinah Daulay (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to examine the effectiveness of group counseling services using the Creative Problem-Solving (CPS) technique in reducing academic stress levels among junior high school students. The background of this research is grounded in the high levels of academic pressure experienced by adolescents, including performance demands, social competition, and expectations from teachers and parents, all of which can trigger academic stress if not properly addressed. CPS, a technique previously widely applied in the development of creative learning, is adapted here as a psychopedagogical intervention strategy in the context of group counseling. This study employed a quasi-experimental approach with a pretest-posttest control group design. The sample consisted of 16 ninth-grade students from SMP Negeri 3 Percut Sei Tuan who were identified as having high levels of academic stress. They were selected using purposive sampling and divided into experimental and control groups. The instrument used was an academic stress scale based on four aspects: physiological, cognitive, affective, and conative. Validity and reliability tests showed that the instrument was both valid and reliable (r = 0.45–0.78; α = 0.86). Data analysis was conducted using a paired samples t-test and an independent samples t-test. The results revealed a significant reduction in academic stress scores in the experimental group, from M = 76.69 to M = 62.44 (p < 0.001), with a Cohen’s d of 2.64, indicating a very large effect size. Meanwhile, the control group did not show a significant change (p > 0.05). These findings demonstrate that the CPS technique in group counseling is effective both statistically and practically in reducing students' academic stress. This study offers a new contribution to the field of educational guidance and counseling by integrating a creative approach to help students manage academic pressures constructively and collaboratively.